Flame-retardant flexible circuit board and preparation method thereof
By applying a crosslinked polyimide coating on the polyimide film of the flexible circuit board and adding fillers, the problems of insufficient flame retardant capacity and degradation of performance at high temperatures are solved, and a higher level of Flame retardant, mechanical and heat resistance.
Patent Information
- Application Number
- CN202411840406.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The flame retardant capacity of existing flexible circuit boards is insufficient and is prone to expand and deform at high temperatures, resulting in a degradation of performance and a risk of equipment fire.
Use polyimide film as the base film and apply a polyimide coating on its surface and lower surface. The cross-linking reaction improves the cross-linking density and stability of the polyimide and increases the filler such as alumina or bis Silicon oxide to improve mechanical properties.
It significantly improves the flame retardant ability, mechanical properties and heat resistance of flexible circuit boards, reduces the risk of fire, and improves its stability and light transmittance at high temperatures.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flexible circuit boards, in particular to a flame retardant flexible circuit board and a preparation method thereof. Background Art
[0002] Flexible Printed Circuit Board, abbreviated as soft board or FPC, is a printed circuit board made of flexible insulating substrate. It can meet the design needs of smaller and higher density installation, help reduce assembly processes and enhance reliability. It can be bent, rolled, and folded freely, and can withstand millions of dynamic bendings without damaging the conductive circuit. It is suitable for the development of electronic products towards high density, miniaturization, and high reliability. The material of the flexible insulating substrate is mainly polyimide or polyester. Polyester film is flammable. The flame retardant ability of polyimide film is relatively good, but there is still room for improvement. It is difficult to form and will expand and deform at high temperatures, resulting in performance degradation. In order to reduce the risk of fire in the equipment and protect the safety of users and equipment. Therefore, we propose a flame retardant flexible circuit board and a preparation method thereof. Summary of the invention
[0003] The object of the present invention is to provide a flame retardant flexible circuit board and a preparation method thereof to solve the problems raised in the above background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a flame retardant flexible circuit board, comprising a base film and a conductive circuit on its surface, wherein the base film comprises a polyimide film and a polyimide coating disposed on the upper and lower surfaces of the polyimide film; Furthermore, the polyimide film is obtained by casting a polyamic acid solution into a film and then imidizing it; The polyamic acid solution includes the following components: a diamine monomer, a dianhydride monomer and a filler.
[0005] Furthermore, the polyimide coating is obtained by coating a crosslinking solution on the surface of a polyimide film and then imidizing it; The cross-linking solution comprises the following components: a diamine monomer, a dianhydride monomer, a cross-linking agent and a filler.
[0006] Furthermore, the filler includes but is not limited to a mixture of one or more of aluminum oxide, silicon oxide, aluminum nitride, polysiloxane, montmorillonite, mica powder, and borosilicate.
[0007] Further, the dianhydride monomer is a mixture of one or more of 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-triphenyl ether tetracarboxylic dianhydride, biphenyl diether dianhydride, 2,2`-difluoromethyl-4,4',5,5'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, 4,4'-terephthaloyl diphthalic anhydride, bisphenol A type diether dianhydride, and pyromellitic acid dianhydride.
[0008] Further, the diamine monomer is 4,4'-diaminodiphenyl ether, 1,4-phenylenediamine, 4,4'-diaminobibenzyl, 4,4'-diaminobiphenyl, 1,4-di(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 5(6)-1-(4-aminophenyl)-1,3,3-trimethylindane (CAS: 54628-90-9), 4,4'-bis(4-aminophenoxy)diphenyl sulfone, 4,4'-bis(3-aminophenoxy)benzophenone, 9,9- A mixture of one or more of bis[4-(4-aminophenoxy)phenyl]fluorene, bis[4-(3-aminophenoxy)phenyl]phenylphosphine oxide, 1,4-phenylenebis[[4-(4-aminophenoxy)phenyl]methanone], 4,4'-[1,4-phenylbis(oxy)]bis[3-(trifluoromethyl)aniline], 1,3-bis(4-aminophenyl)adamantane, 1,3-bis(fluoro-aminophenyl)adamantane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, and 3,7-diamino-2,8-dimethyldibenzothiophene sulfone.
[0009] Furthermore, the cross-linking agent is one of 1,3,5-tris(4-aminophenoxy)benzene and melamine, or a mixture of the two.
[0010] A method for preparing a flame retardant flexible circuit board, comprising the following processes: Step 1, in an organic solvent, mixing a diamine monomer and a dianhydride monomer, stirring for reaction, adding a filler to obtain a polyamic acid solution; casting into a film, drying to form a polyamic acid film; thermal imidization to obtain a polyimide film; Step 2, adding a crosslinking agent to a polyamic acid solution to form a crosslinking solution; coating the crosslinking solution on both surfaces of the polyimide film, drying, to form a polyamic acid coating; thermal imidization to form a polyimide coating to obtain a base film; Step 3: Set up a conductive circuit to obtain a circuit board.
[0011] Further, the polyamic acid solution is prepared by the following process: At a temperature of 3 to 7°C, diamine monomer and organic solvent are mixed, and under the protection of nitrogen atmosphere, 93% to 97% by mass of dianhydride monomer is added, and the reaction is stirred for 60 to 90 minutes; the remaining dianhydride monomer is added, and the reaction is continued with stirring for 4.5 to 5.0 hours to obtain a polyamic acid solution.
[0012] Furthermore, the molar ratio of the dianhydride monomer to the diamine monomer is (1.0-1.5):1.
[0013] Furthermore, the organic solvent is one of dimethyl sulfoxide and dimethylformamide or a mixture of the two.
[0014] Furthermore, the drying process conditions are: temperature 110-125° C., time 10-12 min, to remove the organic solvent.
[0015] Furthermore, the process conditions of thermal imidization are: heating to 280-300°C and keeping warm for 30-40 minutes; taking 30-50°C as the initial temperature, heating by 50°C for 30-40 minutes, and heating rate of 4-5°C / min; after thermal imidization, slowly cooling to room temperature.
[0016] Furthermore, the thickness of the polyimide film is 5 to 60 μm; The cross-linking solution is coated on one side of the polyimide film to a thickness of 20 to 85 μm.
[0017] Furthermore, the amount of the crosslinking agent is 10% to 50% of the amount of the diamine monomer substance.
[0018] Furthermore, the solid content of the polyamic acid solution is 60% to 70%.
[0019] In the above technical scheme, dianhydride monomer and diamine monomer are mixed in an organic solvent, so that the anhydride group and the amino group react to generate an amide acid structure, and a polyamide acid solution is obtained, which has good processing performance, and is cast into a film, dried, and thermally imidized to form a polyimide film. Then the polyamide acid solution is coated on both surfaces of the polyimide film, dried, and solidified to form a polyimide coating to obtain a base film of the circuit board. Finally, a conductive circuit is set on the surface of the base film through copper plating, development, etching, gold plating and other processes, thereby forming a flexible circuit board.
[0020] The dianhydride monomer can be selected from phthalic anhydride, biphenyl anhydride, ether phthalic anhydride, phenylsulfone anhydride, and bisphenol A ether anhydride, which have high rigidity, and the prepared polyimide has better mechanical properties and heat resistance, which is helpful to improve the flame retardancy of the circuit board. And the fluorine-containing dianhydride, by introducing fluorine atoms, its lower molar polarizability can reduce the dielectric constant and dielectric loss of the polyimide, improve the insulation performance and corrosion resistance of the base film, and can enhance its thermal stability and oxidation resistance, improve the heat resistance stability of the base film. And the fluorine atom has a higher electronegativity, which can destroy the electron cloud conjugation with the color-producing functional structure in the polyimide molecular structure, so that the polyimide shows good light transmittance.
[0021] In the above technical solution, the precursor material of the polyimide coating is a mixture of a polyamic acid solution and a crosslinking agent. The crosslinking agent is a polyamino compound. By adjusting the amount of dianhydride monomer, diamine monomer and crosslinking agent, the dianhydride monomer reacts with the diamine monomer and the crosslinking agent, which can effectively improve the crosslinking density of the prepared polyimide (coating), form a network structure, and improve the stability of the polyimide, which significantly improves the mechanical properties, heat resistance and dielectric properties of the prepared polyimide coating.
[0022] Further, the amount of filler is 0.5 to 2.0 wt %; The filler is silica, with a particle size of 2.5 to 20 μm; The silicon dioxide is modified by coupling, and the coupling agent is selected from 4-perfluorotriethoxysilane and M-aminophenyltrimethoxysilane. The specific process is as follows: Disperse silicon dioxide in an alcohol aqueous solution, add ammonia water to adjust the pH to 7.5-9.0, add a coupling agent, stir and react for 6-8 hours; filter and dry to obtain a modified filler; The amount of coupling agent used is 1% to 10% of the mass of silica; the alcohol aqueous solution is ethanol aqueous solution with a concentration of 50 to 90v%, and the ratio of silica to alcohol aqueous solution is (20 to 40) g / 100mL.
[0023] In the above technical solution, silicon dioxide is added to the polyamic acid solution, which can significantly improve the mechanical properties, thermal and dielectric properties of the polyimide film and coating. As a filler, silicon dioxide is coupled and modified, which improves its dispersibility in polyimide and the interfacial bonding between the two, improves the flexibility of polyimide, reduces its thermal expansion coefficient, and helps to further improve the mechanical properties, light transmittance, and heat and flame retardancy of the base film.
[0024] Furthermore, when the polyamic acid contains a reactive amine group, the crosslinking agent may be 2,5-dichloro-p-xylene, 1,3,5-trichlorobenzene, or a polychlorinated compound, and the polychlorinated compound is prepared by the following process: S1. Mix N-(3,4-dihydroxyphenyl)maleimide, hexachlorocyclotriphosphazene, carbon tetrachloride and triethylamine in dichloromethane, heat to 40-60°C, and reflux for 14-15h; distill under reduced pressure and elute to obtain trimaleimide cyclotriphosphazene; S2, mixing allyl DOPO and chlorine-containing maleimide in o-dichlorobenzene, heating to 150-180° C., stirring and reacting for 8-10 hours; precipitating, drying, and obtaining a DOPO derivative; S3. Trimaleimide cyclotriphosphazene and DOPO derivative are mixed in diphenyl ether, and the temperature is raised to 170-200° C. under the protection of nitrogen atmosphere, and the reaction is carried out for 60-150 minutes; methanol is added for precipitation, and vacuum drying is performed to obtain a cross-linking agent.
[0025] Further, in S1, the molar ratio of N-(3,4-dihydroxyphenyl)maleimide, hexachlorocyclotriphosphazene, carbon tetrachloride, and triethylamine is (3.3-3.6):1:(3.3-3.6):(3.3-3.6); The ratio of N-(3,4-dihydroxyphenyl)maleimide to dichloromethane is (8-10) g / 100 mL.
[0026] Further, in S2, the molar ratio of propylene DOPO (CAS No. 311342-65-1) and chlorinated maleimide is 1:1; The chlorine-containing maleimide is a mixture of one or more of 1-(4-chlorophenyl)-pyrrole-2,5-dione, N-(2-chloropyridin-3-yl)maleamide, and N-(3-chloro-2-tolyl)maleimide; Iron phosphate is added as a catalyst in the reaction system, and the amount used is 3% to 5% of the total mass of the reactants; The ratio of propenyl DOPO to o-dichlorobenzene is (3-8) g / 100 mL.
[0027] Furthermore, in S3, the mass ratio of trimaleimidocyclotriphosphazene and DOPO derivative is 10:(20.6-21.2); Nickel perchlorate is added as a catalyst in the reaction system, and the amount used is 3% to 6% of the total mass of the reactants; The ratio of trimaleimidocyclotriphosphazene to diphenyl ether is (3-5) g / 100 mL.
[0028] In the above technical solution, the cross-linking agent can be selected to contain polychlorinated compounds, so that it reacts with the amino groups in the polyamic acid during the thermal imidization process to achieve cross-linking. Compared with the use of amine cross-linking agents, the dianhydride monomer and the diamine monomer have better reactivity, which helps to increase the molecular weight of polyimide, and the resulting coating has better mechanical properties and heat resistance and flame retardancy.
[0029] The crosslinking agent is prepared by the following process: N-(3,4-dihydroxyphenyl) maleimide and hexachlorocyclotriphosphazene are mixed, and under the action of carbon tetrachloride and triethylamine, the catechol in the reactant reacts with two chlorine groups to form a benzodioxaphosphorus structure, forming a trifunctional maleimide compound, which is recorded as trimaleimide cyclotriphosphazene. At high temperature, allyl DOPO is mixed with chlorine-containing maleimide, and the allyl group in allyl DOPO reacts with the double bond in maleimide to form an Alder-ene reaction (ene reaction), thereby obtaining a DOPO compound with alkenyl and chlorine groups, which is recorded as a DOPO derivative. The above-obtained trimaleimide cyclotriphosphazene and DOPO derivatives are mixed, and the maleimide group in the reactant is added to the alkenyl group to perform a DA reaction, thereby obtaining a trifunctional chlorine-containing compound, i.e., a crosslinking agent. When the crosslinking agent is used in the preparation of polyimide, the twisted and non-coplanar structure is introduced into the polyimide system, so that the main chain of the macromolecule presents a deformed and twisted spatial configuration, which effectively inhibits the long-distance transfer of charge along the molecular chain, which can effectively improve the mechanical properties and thermal properties of the prepared polyimide coating. In addition, due to the influence of the twisted and non-coplanar structure, the stacking effect of the molecular chain is weakened, and the intermolecular force and CTC effect are inhibited, which can significantly improve the light transmittance of the prepared polyimide coating.
[0030] And from the above, it can be seen that the cross-linking agent contains structures such as cyclotriphosphazene, benzodioxaphosphine, DOPO, nitrogen heterocycle, cycloalkane, etc., which improve the heat resistance of the base film, inhibit combustion, and reduce the risk of combustion; during combustion, the thermal decomposition will absorb a large amount of heat, reduce the ambient temperature, delay the heating rate of the base film, and inhibit the reaching of the ignition temperature; the decomposition products form a carbonized layer on the surface of the base film, which serves as a protective layer, and cooperates with the non-combustible gas produced by the decomposition to block the transfer of heat and combustible gas, prevent the combustion reaction process, and inhibit the spread of flames, thereby giving the base film good heat resistance and flame retardancy.
[0031] Furthermore, the diamine monomer may be the following components, which are specifically prepared by the following process: Mixing allyl DOPO and 4-maleimidobenzoic acid in o-dichlorobenzene, heating to 150-180°C, stirring and reacting for 8-10 hours; precipitating, drying, and obtaining a maleimide derivative; The maleimide derivative and 4-maleimidobenzoic acid are mixed in diphenyl ether, and the temperature is raised to 170-200°C under the protection of nitrogen atmosphere, and the reaction is carried out for 60-150 minutes; methanol is added for precipitation, and vacuum drying is carried out to obtain a diacid compound; Mix tin chloride, polyphosphoric acid and 1,2,4-triaminobenzene hydrochloric acid, heat to 80-85°C under nitrogen atmosphere, and stir for 150-200 minutes; add diacid compound, heat to 200-210°C, stir and react for 12-14 hours; cool to 75-85°C, precipitate with ice water, filter, deacidify with sodium carbonate solution, neutralize the system pH to 8, filter, chromatographically purify, and elute with ethyl acetate / ethanol to obtain diamine monomer.
[0032] Further, the molar ratio of propylene DOPO and 4-maleimidobenzoic acid is 1:1; Iron phosphate is added as a catalyst in the reaction system, and the amount used is 3% to 5% of the total mass of the reactants; The ratio of propenyl DOPO to o-dichlorobenzene is (3-8) g / 100 mL.
[0033] Furthermore, the mass ratio of 4-maleimidobenzoic acid and maleimide derivative is (5.0-5.5):10; Nickel perchlorate is added as a catalyst in the reaction system, and the amount used is 3% to 6% of the total mass of the reactants; The ratio of maleimide derivative to diphenyl ether is (3-5) g / 100 mL.
[0034] Further, the mass of 1,2,4-triaminobenzene hydrochloric acid and diacid compound is (5.5-6.9):10; The dosage of tin chloride is 2.1% to 2.6% of the mass of 1,2,4-triaminobenzene hydrochloric acid; The amount of polyphosphoric acid used is 9.0 to 9.7 times the mass of 1,2,4-triaminobenzene hydrochloric acid.
[0035] In the above technical scheme, the diamine monomer can select a diamine compound containing an imidazole group, which increases the reactivity. After the reaction of its diamine group with the dianhydride monomer is completed, when the thermal imide process is carried out, its imidazole group reacts with the chlorine group in the cross-linking agent to achieve post-crosslinking of the polyimide coating, and the mechanical properties and heat resistance and flame retardancy of the base film are improved. Continuing the preparation principle of the cross-linking agent, at high temperature, the propylene DOPO reacts with 4-maleimidobenzoic acid to produce an Alder-ene reaction to obtain a maleimide derivative with an olefin group. It is added to 4-maleimidobenzoic acid to obtain a carboxyl compound with difunctionality, which is recorded as a diacid compound. Its carboxyl group reacts with o-phenylenediamine in 1,2,4-triaminobenzene hydrochloric acid to form a benzimidazole structure, thereby obtaining a diamine monomer containing an imidazole group, which increases the rigidity of the prepared polyimide (coating), increases the thermally stable structure, and enhances its mechanical properties and high temperature resistance and flame retardancy.
[0036] In the above technical scheme, the diamine monomer and dianhydride monomer in the structural raw material of the polyimide film are preferably phenyl ether type, fluorine-containing type, copolymerization type of two (or more) dianhydride / amine monomers or the above self-made diamine monomers. Through the introduction of flexible structure, non-coplanar structure, high electronegativity structure, second anhydride or amine, the regularity of the polyimide molecular structure is destroyed, the intermolecular force is reduced, and its solubility in organic solvents is improved. When the surface of the polyimide film is coated with a cross-linking solution, the organic solvent in the cross-linking solution can dissolve the surface of the polyimide film to a certain extent, so that the polyimide film and the cross-linking solution produce an interface fusion (if the diamine monomer in the polyimide film contains a self-made component, it can also react with the self-made cross-linking agent in the cross-linking solution). After thermal imidization, the bonding strength between the sheet structures is significantly improved, which helps to eliminate the material and performance differences between the coating and the film, and improve the comprehensive performance of the prepared base film. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In the following specific embodiments, the thickness of the polyimide film is 35 μm; The cross-linking solution is coated on one side of the polyimide film with a thickness of 20 μm; during the preparation process, after adding the cross-linking agent, an organic solvent is added to adjust the solid content so that it is consistent with the solid content of the polyamic acid solution; The filler selected was silica, JL-SiO2-W06, with an average particle size of 3 μm, sourced from Ningbo Jinlei Nanomaterial Technology Co., Ltd.
[0039] Embodiment 1: A method for preparing a flame retardant flexible circuit board, comprising the following process: Step 1, 1.1. Disperse silica in a 50v% alcohol aqueous solution, add ammonia water to adjust the pH to 7.5, add 4-perfluorotriethoxysilane, and stir the reaction for 6h; filter and dry to obtain a modified filler; the ratio of silica, 4-perfluorotriethoxysilane, and alcohol aqueous solution is 40g / 0.4g / 100mL; 1.2. Mix allyl DOPO, 4-maleimidobenzoic acid and 3% ferric phosphate in o-dichlorobenzene, heat to 150°C, and stir to react for 10 hours; precipitate and dry to obtain a maleimide derivative; the molar ratio of allyl DOPO to 4-maleimidobenzoic acid is 1:1; the ratio of allyl DOPO to o-dichlorobenzene is 8 g / 100 mL; The maleimide derivative, 4-maleimidobenzoic acid and 3% nickel perchlorate were mixed in diphenyl ether, and the temperature was raised to 170°C under nitrogen atmosphere for 150 minutes. Methanol was added for precipitation and vacuum drying to obtain a diacid compound. The mass ratio of 4-maleimidobenzoic acid to maleimide derivative was 5.5:10. The ratio of maleimide derivative to diphenyl ether was 5g / 100mL. 1,2,4-triaminobenzene hydrochloric acid, 2.1% tin chloride and 9.0 times polyphosphoric acid were mixed, heated to 80°C under nitrogen atmosphere protection, and stirred for 200 minutes; a diacid compound was added, the temperature was raised to 200°C, and the reaction was stirred for 14 hours; the temperature was lowered to 75°C, precipitated with ice water, filtered, deacidified with sodium carbonate solution, the pH of the system was neutralized to 8, filtered, purified by chromatography, and eluted with ethyl acetate / ethanol to obtain a diamine monomer; the mass ratio of 1,2,4-triaminobenzene hydrochloric acid to the diacid compound was 5.9:10; 1.3. At a temperature of 3°C, diamine monomer and organic solvent dimethylformamide were mixed, and under the protection of nitrogen atmosphere, 93% by weight of dianhydride monomer was added, and the reaction was stirred for 90 minutes; the remaining dianhydride monomer was added, and the reaction was continued for 5.0 hours, and 0.5wt% of modified filler was added to obtain a polyamic acid solution with a solid content of 60%; the dianhydride monomer was a mixture of 2,3,3',4'-biphenyltetracarboxylic dianhydride and 2,2`-difluoromethyl-4,4',5,5'-biphenyltetracarboxylic dianhydride, and the molar ratio was 9:1; the mass ratio of dianhydride monomer to diamine monomer was 3.5:10; film casting was performed, and drying was performed to form a polyamic acid film; thermal imidization was performed to obtain a polyimide film; Step 2, 2.1. Mix N-(3,4-dihydroxyphenyl)maleimide, hexachlorocyclotriphosphazene, carbon tetrachloride, and triethylamine in dichloromethane, heat to 40°C, and reflux for 15 hours; distill under reduced pressure and elute to obtain trimaleimide cyclotriphosphazene; the molar ratio of N-(3,4-dihydroxyphenyl)maleimide, hexachlorocyclotriphosphazene, carbon tetrachloride, and triethylamine is 3.3:1:3.3:3.3; the ratio of N-(3,4-dihydroxyphenyl)maleimide to dichloromethane is 10 g / 100 mL; Propylene DOPO, chlorinated maleimide and 3% iron phosphate are mixed in o-dichlorobenzene, heated to 150°C, stirred and reacted for 10 hours; precipitated and dried to obtain a DOPO derivative; the molar ratio of propenyl DOPO to chlorinated maleimide is 1:1; the chlorinated maleimide is 1-(4-chlorophenyl)-pyrrole-2,5-dione; the ratio of propenyl DOPO to o-dichlorobenzene is 8 g / 100 mL; The trimaleimide cyclotriphosphazene, DOPO derivative and 3% nickel perchlorate were mixed in diphenyl ether, and the temperature was raised to 170°C under nitrogen atmosphere for 150 minutes; methanol was added for precipitation, and the mixture was dried under vacuum to obtain a crosslinking agent; the mass ratio of trimaleimide cyclotriphosphazene to DOPO derivative was 10:20.6; the ratio of trimaleimide cyclotriphosphazene to diphenyl ether was 5 g / 100 mL; 2.2. Adding a crosslinking agent to the polyamic acid solution, the amount of the crosslinking agent is 23% of the mass of the diamine monomer to form a crosslinking solution; coating the crosslinking solution on both surfaces of the polyimide film, drying, to form a polyamic acid coating; thermal imidization, forming a polyimide coating, to obtain a base film; The drying process is as follows: temperature 125°C, duration 10 minutes; the thermal imidization process is as follows: heating to 280°C, keeping warm for 40 minutes; starting at 30°C, heating up by 50°C, keeping warm for 30 minutes, heating rate 4°C / min; after thermal imidization, slowly cool to room temperature; Step 3: Set up a conductive circuit to obtain a circuit board.
[0040] Embodiment 2: A method for preparing a flame retardant flexible circuit board, comprising the following process: Step 1, 1.1. Disperse silica in a 70v% alcohol aqueous solution, add ammonia water to adjust the pH to 8.2, add M-aminophenyltrimethoxysilane, and stir the reaction for 7h; filter and dry to obtain a modified filler; the ratio of silica, M-aminophenyltrimethoxysilane, and alcohol aqueous solution is 30g / 1.5g / 100mL; 1.2. Mix allyl DOPO, 4-maleimidobenzoic acid and 4% ferric phosphate in o-dichlorobenzene, heat to 165°C, and stir to react for 9 hours; precipitate and dry to obtain a maleimide derivative; the molar ratio of allyl DOPO to 4-maleimidobenzoic acid is 1:1; the ratio of allyl DOPO to o-dichlorobenzene is 5 g / 100 mL; The maleimide derivative, 4-maleimidobenzoic acid and 4.5% nickel perchlorate were mixed in diphenyl ether, and the temperature was raised to 185°C under nitrogen atmosphere for 100 min. Methanol was added for precipitation and vacuum drying to obtain a diacid compound. The mass ratio of 4-maleimidobenzoic acid to maleimide derivative was 5.2:10. The ratio of maleimide derivative to diphenyl ether was 4 g / 100 mL. 1,2,4-triaminobenzene hydrochloric acid, 2.3% tin chloride and 9.3 times polyphosphoric acid were mixed, heated to 82°C under nitrogen atmosphere protection, and stirred for 180 minutes; the diacid compound was added, the temperature was raised to 205°C, and the reaction was stirred for 13 hours; the temperature was lowered to 80°C, precipitated with ice water, filtered, deacidified with sodium carbonate solution, the pH of the system was neutralized to 8, filtered, purified by chromatography, and eluted with ethyl acetate / ethanol to obtain a diamine monomer; the mass ratio of 1,2,4-triaminobenzene hydrochloric acid to the diacid compound was 6.6:10; 1.3. At a temperature of 5°C, diamine monomer and organic solvent dimethylformamide were mixed, and under the protection of nitrogen atmosphere, 95% by weight of dianhydride monomer was added, and the reaction was stirred for 75 minutes; the remaining dianhydride monomer was added, and the reaction was continued for 4.8 hours, and 1.2wt% of modified filler was added to obtain a polyamic acid solution with a solid content of 65%; the dianhydride monomer was a mixture of biphenyl diether dianhydride and 2,2`-difluoromethyl-4,4',5,5'-biphenyltetracarboxylic acid dianhydride, and the molar ratio was 8:2; the mass ratio of dianhydride monomer to diamine monomer was 5.3:10; film casting was performed, and dried to form a polyamic acid film; thermal imidization was performed to obtain a polyimide film; Step 2, 2.1. Mix N-(3,4-dihydroxyphenyl)maleimide, hexachlorocyclotriphosphazene, carbon tetrachloride, and triethylamine in dichloromethane, heat to 50°C, and reflux for 14.5h; distill under reduced pressure and elute to obtain trimaleimide cyclotriphosphazene; the molar ratio of N-(3,4-dihydroxyphenyl)maleimide, hexachlorocyclotriphosphazene, carbon tetrachloride, and triethylamine is 3.5:1:3.5:3.5; the ratio of N-(3,4-dihydroxyphenyl)maleimide to dichloromethane is 9g / 100mL; Propylene DOPO, chloromaleimide and 4% ferric phosphate are mixed in o-dichlorobenzene, heated to 165°C, stirred and reacted for 9 hours; precipitated and dried to obtain a DOPO derivative; the molar ratio of propenyl DOPO to chloromaleimide is 1:1; the chloromaleimide is N-(2-chloropyridin-3-yl)maleamide; the ratio of propenyl DOPO to o-dichlorobenzene is 5g / 100mL; The trimaleimide cyclotriphosphazene, DOPO derivative and 4.5% nickel perchlorate were mixed in diphenyl ether, and the temperature was raised to 185°C under nitrogen atmosphere for 100 min. Methanol was added for precipitation and vacuum drying to obtain a crosslinking agent. The mass ratio of trimaleimide cyclotriphosphazene to DOPO derivative was 10:20.9. The ratio of trimaleimide cyclotriphosphazene to diphenyl ether was 4 g / 100 mL. 2.2. Adding a crosslinking agent to the polyamic acid solution, the amount of the crosslinking agent is 35% of the mass of the diamine monomer to form a crosslinking solution; coating the crosslinking solution on both surfaces of the polyimide film, drying, to form a polyamic acid coating; thermal imidization, forming a polyimide coating, to obtain a base film; The drying process is as follows: temperature 120°C, duration 11 minutes; the thermal imidization process is as follows: heating to 290°C, keeping warm for 35 minutes; starting at 40°C, heating up by 50°C, keeping warm for 35 minutes, heating rate 4.5°C / min; after thermal imidization, slowly cool to room temperature; Step 3: Set up a conductive circuit to obtain a circuit board.
[0041] Embodiment 3: A method for preparing a flame-retardant flexible circuit board, comprising the following process: Step 1, 1.1. Disperse silica in an alcohol aqueous solution, add ammonia water to adjust the pH to 9.0, add 4-perfluorotriethoxysilane, and stir to react for 8 hours; filter and dry to obtain a modified filler; the ratio of silica, 4-perfluorotriethoxysilane, and alcohol aqueous solution is 20g / 2g / 100mL; 1.2. Mix allyl DOPO, 4-maleimidobenzoic acid and 5% ferric phosphate in o-dichlorobenzene, heat to 180°C, and stir to react for 8 hours; precipitate and dry to obtain a maleimide derivative; the molar ratio of allyl DOPO to 4-maleimidobenzoic acid is 1:1; the ratio of allyl DOPO to o-dichlorobenzene is 3 g / 100 mL; The maleimide derivative, 4-maleimidobenzoic acid and 6% nickel perchlorate were mixed in diphenyl ether, and the temperature was raised to 200°C under nitrogen atmosphere for 60 minutes. Methanol was added for precipitation, and the mixture was dried under vacuum to obtain a diacid compound. The mass ratio of 4-maleimidobenzoic acid to maleimide derivative was 5.5:10. The ratio of maleimide derivative to diphenyl ether was 3 g / 100 mL. Mix 1,2,4-triaminobenzene hydrochloric acid, 2.6% tin chloride and 9.7 times polyphosphoric acid, heat to 85°C under nitrogen atmosphere, and stir for 150 minutes; add diacid compound, heat to 210°C, and stir for 12 hours; cool to 85°C, precipitate with ice water, filter, deacidify with sodium carbonate solution, neutralize the system pH to 8, filter, chromatographically purify, and elute with ethyl acetate / ethanol to obtain diamine monomer; the mass ratio of 1,2,4-triaminobenzene hydrochloric acid to diacid compound is 7.3:10; 1.3. At 7°C, diamine monomer and organic solvent dimethylformamide were mixed, and under nitrogen atmosphere, 97% by weight of dianhydride monomer was added, and the reaction was stirred for 60 minutes; the remaining dianhydride monomer was added, and the reaction was continued for 4.5 hours, and 2.0wt% of modified filler was added to obtain a polyamic acid solution with a solid content of 70%; the dianhydride monomer was a mixture of 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride and 2,2`-difluoromethyl-4,4',5,5'-biphenyltetracarboxylic dianhydride, and the molar ratio was 7:3; the mass ratio of dianhydride monomer to diamine monomer was 3.7:10; film casting was performed, and dried to form a polyamic acid film; thermal imidization was performed to obtain a polyimide film; Step 2, 2.1. Mix N-(3,4-dihydroxyphenyl)maleimide, hexachlorocyclotriphosphazene, carbon tetrachloride, and triethylamine in dichloromethane, heat to 60°C, and reflux for 14 hours; distill under reduced pressure and elute to obtain trimaleimide cyclotriphosphazene; the molar ratio of N-(3,4-dihydroxyphenyl)maleimide, hexachlorocyclotriphosphazene, carbon tetrachloride, and triethylamine is 3.6:1:3.6:3.6; the ratio of N-(3,4-dihydroxyphenyl)maleimide to dichloromethane is 8 g / 100 mL; Propylene DOPO, chlorine-containing maleimide and 5% ferric phosphate are mixed in o-dichlorobenzene, heated to 180°C, stirred and reacted for 8 hours; precipitated and dried to obtain a DOPO derivative; the molar ratio of propenyl DOPO to chlorine-containing maleimide is 1:1; the chlorine-containing maleimide is N-(3-chloro-2-methylphenyl) maleimide; the ratio of propenyl DOPO to o-dichlorobenzene is 3g / 100mL; The trimaleimide cyclotriphosphazene, DOPO derivative and 6% nickel perchlorate were mixed in diphenyl ether, and the temperature was raised to 200°C under nitrogen atmosphere for 60 minutes; methanol was added for precipitation, and vacuum drying was performed to obtain a crosslinking agent; the mass ratio of trimaleimide cyclotriphosphazene to DOPO derivative was 10:21.2; the ratio of trimaleimide cyclotriphosphazene to diphenyl ether was 3 g / 100 mL; 2.2. Adding a crosslinking agent to the polyamic acid solution, the amount of the crosslinking agent is 46% of the mass of the diamine monomer to form a crosslinking solution; coating the crosslinking solution on both surfaces of the polyimide film, drying, to form a polyamic acid coating; thermal imidization, forming a polyimide coating, to obtain a base film; The drying process is: temperature 110℃, duration 12min; the thermal imidization process is: heating to 300℃, keeping warm for 40min; starting at 50℃, heating up by 50℃, keeping warm for 40min, heating rate 5℃ / min; after thermal imidization, slowly cool to room temperature; Step 3: Set up a conductive circuit to obtain a circuit board.
[0042] Comparative Example 1: A method for preparing a flame-retardant flexible circuit board, comprising the following processes: Step 1, 1,2,4-triaminobenzene hydrochloric acid, 2.6% tin chloride and 9.7 times polyphosphoric acid are mixed, heated to 85°C under nitrogen atmosphere protection, and stirred for 150 minutes; terephthalic acid is added, the temperature is raised to 210°C, and the reaction is stirred for 12 hours; the temperature is lowered to 85°C, precipitated with ice water, filtered, deacidified with sodium carbonate solution, the pH of the system is neutralized to 8, filtered, purified by chromatography, eluted with ethyl acetate / ethanol, and a diamine monomer is obtained; the molar ratio of 1,2,4-triaminobenzene hydrochloric acid to terephthalic acid is 2.4:1; At a temperature of 3°C, a diamine monomer and an organic solvent, dimethylformamide, are mixed, and under the protection of a nitrogen atmosphere, 93% by weight of a dianhydride monomer is added, and the reaction is stirred for 90 minutes; the remaining dianhydride monomer is added, and the reaction is continued for 5.0 hours, and 0.5wt% of silicon dioxide is added to obtain a polyamic acid solution with a solid content of 60%; the dianhydride monomer is a mixture of 2,3,3',4'-biphenyltetracarboxylic dianhydride and 2,2`-difluoromethyl-4,4',5,5'-biphenyltetracarboxylic dianhydride, and the molar ratio is 9:1; the mass ratio of the dianhydride monomer to the diamine monomer is 7.5:10; film casting is performed, and drying is performed to form a polyamic acid film; thermal imidization is performed to obtain a polyimide film; Steps 2 and 3 are the same as those in Example 1 to obtain a circuit board.
[0043] Comparative Example 2: A method for preparing a flame-retardant flexible circuit board, comprising the following processes: Step 1, 1,2,4-triaminobenzene hydrochloric acid, 2.6% tin chloride and 9.7 times polyphosphoric acid are mixed, heated to 85°C under nitrogen atmosphere protection, and stirred for 150 minutes; terephthalic acid is added, the temperature is raised to 210°C, and the reaction is stirred for 12 hours; the temperature is lowered to 85°C, precipitated with ice water, filtered, deacidified with sodium carbonate solution, the pH of the system is neutralized to 8, filtered, purified by chromatography, eluted with ethyl acetate / ethanol, and a diamine monomer is obtained; the molar ratio of 1,2,4-triaminobenzene hydrochloric acid to terephthalic acid is 2.4:1; At a temperature of 3°C, a diamine monomer and an organic solvent, dimethylformamide, are mixed, and under the protection of a nitrogen atmosphere, 93% by weight of a dianhydride monomer is added, and the reaction is stirred for 90 minutes; the remaining dianhydride monomer is added, and the reaction is continued for 5.0 hours, and 0.5wt% of silicon dioxide is added to obtain a polyamic acid solution with a solid content of 60%; the dianhydride monomer is a mixture of 2,3,3',4'-biphenyltetracarboxylic dianhydride and 2,2`-difluoromethyl-4,4',5,5'-biphenyltetracarboxylic dianhydride, and the molar ratio is 9:1; the mass ratio of the dianhydride monomer to the diamine monomer is 7.5:10; film casting is performed, and drying is performed to form a polyamic acid film; thermal imidization is performed to obtain a polyimide film; Steps 2 and 3 are the same as those in Example 1, and the cross-linking agent is 2,5-dichloroparaxylene, and the amount used is 20% of the amount of the diamine monomer substance to obtain a circuit board.
[0044] Comparative Example 3: A method for preparing a flame-retardant flexible circuit board, comprising the following processes: Step 1, at a temperature of 3°C, a diamine monomer 4,4'-diaminodiphenyl ether and an organic solvent dimethylformamide are mixed, and under the protection of a nitrogen atmosphere, 93% by weight of a dianhydride monomer is added, and the reaction is stirred for 90 minutes; the remaining dianhydride monomer is added, and the reaction is continued for 5.0 hours, and 0.5wt% of silicon dioxide is added to obtain a polyamic acid solution with a solid content of 60%; the dianhydride monomer is a mixture of 2,3,3',4'-biphenyltetracarboxylic dianhydride and 2,2`-difluoromethyl-4,4',5,5'-biphenyltetracarboxylic dianhydride, and the molar ratio is 9:1; the molar ratio of the dianhydride monomer to the diamine monomer is 1:1.2; film casting, drying, forming a polyamic acid film; thermal imidization, obtaining a polyimide film; Steps 2 and 3 are the same as in Example 1, and the amount of the cross-linking agent used is 20% of the amount of the diamine monomer substance to obtain a circuit board.
[0045] Comparative Example 4: A method for preparing a flame-retardant flexible circuit board, comprising the following processes: Steps 1, 2, and 3 are the same as those in Comparative Example 3, the dianhydride monomer is 2,3,3',4'-biphenyltetracarboxylic dianhydride; the molar ratio of the dianhydride monomer to the diamine monomer is 1.2:1; the cross-linking agent is 1,3,5-tri(4-aminophenoxy)benzene, and the amount used is 20% of the amount of the diamine monomer substance, to obtain a circuit board.
[0046] Comparative Example 5: A method for preparing a flame-retardant flexible circuit board, comprising the following processes: Steps 1 and 3 are the same as those in Comparative Example 4; the dianhydride monomer is 4,4'-terephthalamide diphthalic anhydride, and the molar ratio of the dianhydride monomer to the diamine monomer is 1:1. Step 2 comprises coating a polyamic acid solution on both surfaces of the polyimide film, drying the film, and forming a polyamic acid coating film; performing thermal imidization to form a polyimide coating, obtaining a base film, and obtaining a circuit board.
[0047] Experiment: Take the base film plates obtained in Examples 1-3 and Comparative Examples 1-5, prepare samples, test their properties respectively and record the test results: Mechanical properties test: GB / T 1040 was used as the reference standard, and a universal testing machine was used to test the tensile properties of the base film sample at a tensile rate of 50 mm / min; Dielectric performance test: Use an impedance analyzer to measure the dielectric constant of the base film sample at a frequency of 10MHz; High temperature flame retardant performance test: Use static mechanical analyzer to detect the thermal expansion coefficient of the sample in a nitrogen atmosphere. The heat treatment temperature is 250℃ and the heat treatment time is 2h. Taking GB / T 2409 as the reference standard, a vertical burning tester was used to conduct a vertical burning test on the base film sample to determine its flame retardant grade (UL-94); Light transmittance test: A UV-visible spectrometer was used to detect the light transmittance of the coating sample at 400 nm. The thickness of the polyimide coating was 20 μm.
[0048] According to the data in the above table, we can clearly draw the following conclusions: The basement membranes obtained in Examples 1-3 are compared with the basement membranes obtained in Comparative Examples 1-5. The test results show that: Compared with the comparative example, the base films obtained in Examples 1-3 have higher tensile strength, dielectric constant, flame retardant grade and light transmittance data, and lower thermal expansion coefficient data. This fully demonstrates that the present invention achieves improvements in the mechanical properties, dielectric properties, high temperature flame retardant properties and light transmittance of the prepared base films.
[0049] Compared with Example 1, the preparation process of the diamine monomer in the polyimide film and the polyimide coating of Comparative Example 1 is different; the diamine monomer in the polyimide film and the polyimide coating of Comparative Example 2 is 4,4'-diaminodiphenyl ether; the diamine monomer in Comparative Example 3 is the same as that in Comparative Example 1, and the cross-linking agent is 2,5-dichloroparaxylene. Compared with Comparative Example 2, the cross-linking agent in Comparative Example 4 is 1,3,5-tris(4-aminophenoxy)benzene; no cross-linking agent is provided in Comparative Example 5. The flame retardant grade of the base film obtained in Comparative Examples 1-5 is significantly reduced, and the tensile strength, dielectric constant, thermal expansion coefficient and light transmittance data are deteriorated. It can be seen that the setting of the base film preparation process and the components used in the present invention can promote the comprehensive improvement of its mechanical properties, dielectric properties, high temperature flame retardant properties and light transmittance.
[0050] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a flame retardant flexible circuit board, characterized in that: Including the following processes: Step 1, in an organic solvent, mixing a diamine monomer and a dianhydride monomer, stirring for reaction, adding a filler, and obtaining a polyamic acid solution; Casting into film, drying to form a polyamic acid film; Thermal imidization to obtain a polyimide film; Step 2, adding a crosslinking agent to the polyamic acid solution to form a crosslinking solution; Coating a crosslinking solution on both surfaces of a polyimide film and drying the film to form a polyamic acid coating; Thermal imidization to form a polyimide coating to obtain a base film; Step 3: Set up a conductive circuit to obtain a circuit board.
2. The method for preparing a flame-retardant flexible circuit board according to claim 1, characterized in that: The dianhydride monomer is a mixture of one or more of 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-triphenyl ether tetracarboxylic dianhydride, biphenyl diether dianhydride, 2,2`-difluoromethyl-4,4',5,5'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, 4,4'-terephthaloyl diphthalic anhydride, bisphenol A type diether dianhydride, and pyromellitic acid dianhydride.
3. The method for preparing a flame-retardant flexible circuit board according to claim 1, characterized in that: The diamine monomers are 4,4'-diaminodiphenyl ether, 1,4-phenylenediamine, 4,4'-diaminobibenzyl, 4,4'-diaminobiphenyl, 1,4-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 5(6)-1-(4-aminophenyl)-1,3,3-trimethylindane, 4,4'-bis(4-aminophenoxy)diphenyl sulfone, 4,4'-bis(3-aminophenoxy)benzophenone, 9,9-bis[4-(4-aminophenoxy)phenyl]propane, A mixture of one or more of bis[4-(4-aminophenoxy)phenyl]fluorene, bis[4-(3-aminophenoxy)phenyl]phenylphosphine oxide, 1,4-phenylenebis[[4-(4-aminophenoxy)phenyl]methanone], 4,4'-[1,4-phenylbis(oxy)]bis[3-(trifluoromethyl)aniline], 1,3-bis(4-aminophenyl)adamantane, 1,3-bis(fluoro-aminophenyl)adamantane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, and 3,7-diamino-2,8-dimethyldibenzothiophene sulfone.
4. The method for preparing a flame-retardant flexible circuit board according to claim 1, characterized in that: The cross-linking agent is one of 1,3,5-tris(4-aminophenoxy)benzene and melamine or a mixture of the two.
5. The method for preparing a flame retardant flexible circuit board according to claim 4, characterized in that: The molar ratio of the dianhydride monomer to the diamine monomer is (1.0-1.5):1; The amount of the cross-linking agent is 10% to 50% of the amount of the diamine monomer substance.
6. The method for preparing a flame retardant flexible circuit board according to claim 1, characterized in that: The process conditions of the thermal imidization are: heating to 280-300° C. and keeping the temperature for 30-40 minutes.
7. The method for preparing a flame retardant flexible circuit board according to claim 1, characterized in that: The cross-linking agent is prepared by the following process: N-(3,4-dihydroxyphenyl)maleimide, hexachlorocyclotriphosphazene, carbon tetrachloride and triethylamine are mixed in dichloromethane, heated to 40-60°C, and refluxed for 14-15h to obtain trimaleimide cyclotriphosphazene; Mixing allyl DOPO and chlorine-containing maleimide in o-dichlorobenzene, heating to 150-180° C., stirring and reacting for 8-10 hours, to obtain a DOPO derivative; The trimaleimide cyclotriphosphazene and DOPO derivative are mixed in diphenyl ether, and the temperature is raised to 170-200° C. under the protection of nitrogen atmosphere, and the reaction is performed for 60-150 minutes to obtain a crosslinking agent.
8. The method for preparing a flame-retardant flexible circuit board according to claim 7, characterized in that: The diamine monomer also includes the following components, which are specifically prepared by the following process: Mixing allyl DOPO and 4-maleimidobenzoic acid in o-dichlorobenzene, heating to 150-180° C., stirring and reacting for 8-10 hours, to obtain a maleimide derivative; Mixing maleimide derivative and 4-maleimidobenzoic acid in diphenyl ether, heating to 170-200° C. under nitrogen atmosphere, reacting for 60-150 min to obtain a diacid compound; Tin chloride, polyphosphoric acid and 1,2,4-triaminobenzene hydrochloric acid are mixed, heated to 80-85°C under nitrogen atmosphere, and stirred for 150-200 minutes; a diacid compound is added, the temperature is raised to 200-210°C, and the reaction is stirred for 12-14 hours to obtain a diamine monomer.
9. The method for preparing a flame-retardant flexible circuit board according to claim 1, characterized in that: The amount of the filler is 0.5-2.0wt%; the filler is silicon dioxide, the silicon dioxide is coupled and modified, and the coupling modifier is selected from 4-perfluorotriethoxysilane and M-aminophenyltrimethoxysilane.
10. A flame retardant flexible circuit board prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Printed wiring board and method for manufacturing same
CN101940074A
Two-layer-method double-sided flexible copper clad laminate and manufacturing method thereof
CN105644055A
Thermal fusion multilayer polyimide film using crosslinked water-soluble thermoplastic polyamic acid, and preparation method thereof
CN107207747A
Polyimide composition, flexible wiring board and method for producing the flexible wiring board
JP2008037915A
Thermoplastic polyimide, crosslinked polyimide, adhesive film, laminate, cover lay film, copper foil with resin, metal-clad laminate, circuit board and multilayer circuit board
JP2023035477A
Cited By
Surface antioxidant for tinned circuit board and preparation method of surface antioxidant
CN119875498A
Thin film used on integrated circuit copper-clad plate
CN122421794A